Public transport selection among young adults : the case of mass rapid transit and university students - Mi, Tinghao; Mohd Helmi Ali, (Pusat Hal Ehwal Pelajar, Universiti Kebangsaan Malaysia, 2018)
This paper investigates specifically what drives young adults to choose Mass Rapid Transit (MRT). From the perspective of young adults, this paper reveals the real demand and the attraction of MRT. To deliver their thoughts and opinions effectively, in-depth interviews were performed with 15 respondents among UKM students. The findings identified the element of low price, convenience, reduced traffic congestion, environmental protection, time-saving, good condition, safety, high efficiency, good enjoyment and more business opportunities as the factors for young adults to use public transport. In addition, the research found that inconvenience in a certain part of the service, insufficient information, small coverage and outdated management as the impeding factor for public transport usage.